Geomechanical Characteristics of Hydrate-bearing Sands ... - Abbas, Muhammad (Graduate Studies, 2018)
This thesis presents an experimental study on the geomechanical characteristics of lab-synthesized methane hydrate bearing sand. Sand was tested in four different states, namely, base sand (BS), frozen sand (FS), gas-saturated hydrate bearing sand (HS), and water-saturated hydrate bearing sand (WHS). Test specimens were evaluated for permeability, stiffness and triaxial strength. It was found that hydrate formation caused a reduction in permeability and a large increase in stiffness of sand. Triaxial test results indicate that both hydrate and ice increased the strength of sand and induced strain-softening behavior. However, HS showed higher peak strength than FS and exhibited different deformation characteristics. Stiffness and triaxial strength of WHS were lower than HS possibly due to marginal hydrate dissociation leading to a potential loss of cementation during water-saturation. The existence of inter-granular cementation in WHS was validated by analysis of experimental data using stress-dilatancy ...